Effects of Dietary Standardized Ileal Digestible Valine:Lysine Ratio on 14 to 22 lb Nursery Pigs - A. B. Clark; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; K. Touchette; R. D. Goodband; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 280 nursery pigs (PIC 327 × 1050; initially 14.4 lb BW) were used in a 28-d growth trial to evaluate the effects of increasing dietary standardized ileal digestible (SID) Valine:Lysine (Val:Lys) ratio on nursery pig growth performance. Pigs were weaned at approximately 21 d of age and allotted to pens according to BW and gender. A common starter diet was fed for 5 d, and then pens were allotted to 1 of 7 dietary treatments in a randomized complete block design according to BW. Experimental diets were fed for 14 d, which included SID valine concentrations of 50, 57, 63, 68, 73, 78, and 85% of Lys. Then pigs were fed a common Phase 3 diet for 14 d. From d 0 to 14, when experimental diets were fed, ADG, ADFI, and F/G improved (quadratic, P<0.036) as SID Val:Lys ratio increased. For ADG, the best-fitting model was the broken line linear (BLL). This model resulted in a maximum ADG to be achieved when feeding a minimum of 62.9% SID Val:Lys ratio. For ADFI, the quadratic polynomial (QP) was the best fitting model, predicting maximum feed intake at 73.7% SID Val:Lys ratio and 99% of maximum performance achieved with 68.0% SID Val:Lys ratio. For feed efficiency, modeled as G:F, the best-fitting model was the QP, estimating maximum G:F at 71.7% SID Val:Lys ratio. In conclusion, this experiment demonstrated that the SID valine requirement for 14 to 22 lb nursery pigs ranged from 62.9 to 73.7% of Lys depending on the response criteria modeled.
Keywords: valine; growth; nursery pigs; swine